The Sound of Progress: Investigating the Representation of Artificial Intelligence in Music - Banh, Leonardo; Strobel, Gero (Wirtschaftsinformatik 2023 Proceedings, 2023)
The role of artificial intelligence in daily life is constantly advancing and has become an important topic of discussion. With music and its lyrics being a vehicle to express topics of society, this paper investigates how artificial intelligence is perceived by musicians and reflected in their songs. By analyzing the lyrics of over 1,200 songs over three decades, this work applies sentiment analysis to extract polarities and emotions. The results provide insights into how musicians view and reflect the impact of artificial intelligence on society and how this is reflected in their song texts. The findings show an increase in songs mentioning artificial intelligence-related terms, with a trend of more songs implying negativity, such as anger. However, minor increases in positive emotions indicate musicians' ambivalent views on hopes and fear of artificial intelligence.
Keywords: Artificial Intelligence; Sentiment Analysis; Music; Lyrics